1990
DOI: 10.1007/bf00058837
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of halogenated aromatic compounds

Abstract: Due to their persistence, haloaromatics are compounds of environmental concern. Aerobically, bacteria degrade these compounds by mono- or dioxygenation of the aromatic ring. The common intermediate of these reactions is (halo)catechol. Halocatechol is cleaved either intradiol (ortho-cleavage) or extradiol (meta-cleavage). In contrast to ortho-cleavage, meta-cleavage of halocatechols yields toxic metabolites. Dehalogenation may occur fortuitously during oxygenation. Specific dehalogenation of aromatic compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
39
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 145 publications
2
39
0
1
Order By: Relevance
“…3). Enzyme-catalyzed C-0-C bond cleavage of PCDDs has not been observed previously (5,9,21). This reaction is catalyzed by LiP alone, albeit at a slow rate.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…3). Enzyme-catalyzed C-0-C bond cleavage of PCDDs has not been observed previously (5,9,21). This reaction is catalyzed by LiP alone, albeit at a slow rate.…”
mentioning
confidence: 63%
“…Since PCDDs are relatively chemically stable and lipophilic in nature (25,40,43), their accumulation in the food chain has been predicted and observed (3,14,29,36). In addition, studies have concluded that these compounds are degraded very slowly by soil bacteria (9,38,41), probably increasing their environmental impact.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, small-molecule PSMA ligands bind to the active site in the extracellular domain of PSMA and are internalized and endosomally recycled, leading to enhanced tumor uptake and retention and high image quality (24)(25)(26)(27). The most widely used 68 Ga-labeled PSMA ligands for PET imaging are 68 Ga-PSMA-11 ( 68 Ga-PSMA-HBED-CC) and the theranostic agents 68 Ga-PSMA-617 and 68 Ga-PSMA-I&T (28,29).…”
mentioning
confidence: 99%
“…These bacterial species have attracted significant research attention for their possible employment as bioremediation agents (2)(3)(4)(5). Of particular interest is the soil-dwelling microbe, Pseudomonas sp.…”
mentioning
confidence: 99%